Anniversary dates in the history of morphology in 2011 - Kutya, S. A. (Морфологія / Morphologia / Morfologìâ, 2011)
500 years ago, Michael Servetus was born (Michael Servetus, 1511-1553) - a Spanish thinker and physician. The first in Europe was the idea of the existence of lung circulation and predicted its physiological meaning. He graduated from the Faculty of Medicine in Paris.